The Quality of Spermatozoa of Gembrong Goats during Cryopreservation Process - F Pamungkas; A Batubara; Sutoro Sutoro (Media Peternakan, 2014)
Gembrong goat is an Indonesia local goat having specific characteristic that is currently categorized as a breed that is at risk of extinction. In this context, the cryopreservation of gametes is important to support a genome resource bank for storage of gametes for an indefinite period of time. Evaluation of semen and spermatozoa quality was performed to determine the survival of spermatozoa and this information will be used as a reference in the cryopreservation of semen and spermatozoa. The aim of this experiment was to study the characteristics of Gembrong goat’s semen and spermatozoa during cryopreservation process. Once a week, semen from three Gembrong goats (ages about 2-3 years old) was collected using artificial vagina and then frozen with TRIS extender. After freezing, the semen was thawed. Macro- and microscopic parameters of semen and spermatozoa were assessed in fresh and frozen-thawed semen. Results showed that in the fresh semen, the volume was 0.5 mL, sperm abnormalities was 5.74%, sperm concentration was 6731 x 106/mL, the sperm motility was 78.33%, live sperm was 83.17%, and sperm membrane integrity was 78.53%. After-thawing observation showed that sperm motility decreased to 49% (P